Домінанти системи попередньої інформації про пасажирів на авіаційному транспорті - Фрадинський, Олександр Анатолійович (Причорноморський науково-дослідний інститут економіки та інновацій, 2017)
У статті досліджено питання організації збору та передачі інформації про пасажирів на авіаційному транспорті в контексті забезпечення безпеки перевезень та організації протидії міжнародному тероризму. Проаналізовано системи попереднього інформування, з’ясовано проблемні питання, які стоять на заваді їх глобального запровадження, окреслено можливості для більш активного використання світовою спільнотою.

The concept of an Advance Passenger Information (API) system was frst developed to meet the needs of the Customs services of certain States, in order to address problems of drug traffcking and threats to national security, as well as to respond to growing international traffc. Advance Passenger Information System governs the provision of a limited number of data elements (identifcation details from the passport and basic ﬂight information) from commercial airline and vessel operators to the computer system of the destination state. Required information should conform to specifcations for UN / EDIFAKT Passenger List Message (PAXLST) formats.
Dominant of advance passenger information on air transport
Keywords: безпека; авіаційний транспорт; пасажир; тероризм; попередня інформація; митниця; кордон; safety; air transport; passenger; terrorism; preliminary information; customs; border